Ответ:
Объяснение:
2m²n³
m=-0.2 n=-5 2*(-0,2)²*(-5)³=2*0,04*(-125)=-10
если m = -0,2; n = -5
2 · (-0,2)² · (-5)³ = -10
1) (-0,2)² = (-0,2) · (-0,2) = 0,04
2) 2 · 0,04 = 0,08
3) (-5)³ = (-5) · (-5) · (-5) = -125
4) 0,08 · (-125) = -10
Ответ: -10.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
2m²n³
m=-0.2 n=-5 2*(-0,2)²*(-5)³=2*0,04*(-125)=-10
Verified answer
2m²n³
если m = -0,2; n = -5
2 · (-0,2)² · (-5)³ = -10
1) (-0,2)² = (-0,2) · (-0,2) = 0,04
2) 2 · 0,04 = 0,08
3) (-5)³ = (-5) · (-5) · (-5) = -125
4) 0,08 · (-125) = -10
Ответ: -10.